Management of opioid use disorder and associated conditions among hospitalized adults: A Consensus Statement from the Society of Hospital Medicine. Issue 9 (26th July 2022) - Calcaterra, Susan L.; Martin, Marlene; Bottner, Richard; Englander, Honora; Weinstein, Zoe; Weimer, Melissa B.; Lambert, Eugene; Herzig, Shoshana J.
Abstract: Hospital‐based clinicians frequently care for patients with opioid withdrawal or opioid use disorder (OUD) and are well‐positioned to identify and initiate treatment for these patients. With rising numbers of hospitalizations related to opioid use and opioid‐related overdose, the Society of Hospital Medicine convened a working group to develop a Consensus Statement on the management of OUD and associated conditions among hospitalized adults. The guidance statement is intended for clinicians practicing medicine in the inpatient setting (e.g., hospitalists, primary care physicians, family physicians, advanced practice nurses, and physician assistants) and is intended to apply to hospitalized adults at risk for, or diagnosed with, OUD. To develop the Consensus Statement, the working group conducted a systematic review of relevant guidelines and composed a draft statement based on extracted recommendations. Next, the working group obtained feedback on the draft statement from external experts in addiction medicine, SHM members, professional societies, harm reduction organizations and advocacy groups, and peer reviewers. The iterative development process resulted in a final Consensus Statement consisting of 18 recommendations covering the following topics: (1) identification and treatment of OUD and opioid withdrawal, (2) perioperative and acute pain management in patients with OUD, and (3) methods to optimize care transitions at hospital discharge for patients with OUD. Most recommendations in the Consensus Statement were derived from guidelines based on observational studies and expert consensus. Due to the lack of rigorous evidence supporting key aspects of OUD‐related care, the working group identified important issues necessitating future research and exploration.